2013
DOI: 10.1111/nep.12131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysis modality and membrane flux on insomnia severity in haemodialysis patients

Abstract: This study indicates that different haemodialysis modalities are associated with insomnia and suggests a potential benefit of using high flux membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…En revanche, dans cette même étude, les patients dialysés depuis moins d'un an étaient moins enclins à la dépression, ce qui est surprenant étant donné qu'insomnie et dépression sont souvent associées en hémodialyse, comme c'est le cas pour Kao notamment [ 11 ]. Knezevigh s'est en revanche intéressé à l'impact des modalités d'hémodialyse sur la survenue et la sévérité de l'insomnie à travers une étude menée sur 122 patients répartis entre hémodialyse avec membrane high flux, low flux et hémodiafiltration [ 12 ]. Son analyse statistique révèle que la sévérité de l'insomnie jugée selon le score ISI (Insomnia severity index) est plus marquée chez les patients en hémodialyse low flux que chez ceux en hémodialyse high flux.…”
Section: Discussionunclassified
“…En revanche, dans cette même étude, les patients dialysés depuis moins d'un an étaient moins enclins à la dépression, ce qui est surprenant étant donné qu'insomnie et dépression sont souvent associées en hémodialyse, comme c'est le cas pour Kao notamment [ 11 ]. Knezevigh s'est en revanche intéressé à l'impact des modalités d'hémodialyse sur la survenue et la sévérité de l'insomnie à travers une étude menée sur 122 patients répartis entre hémodialyse avec membrane high flux, low flux et hémodiafiltration [ 12 ]. Son analyse statistique révèle que la sévérité de l'insomnie jugée selon le score ISI (Insomnia severity index) est plus marquée chez les patients en hémodialyse low flux que chez ceux en hémodialyse high flux.…”
Section: Discussionunclassified
“…Many clinical effects for online HDF have been reported. These include the reduction of dialysis-related hypotension [6], improvement of anemia with sparing erythropoiesis-stimulating agent dosage [7,8,9], prevention of the deterioration of dialysis-related amyloidosis, improvement of the nutritional status by reducing inflammatory stress [10], cardiovascular protection by preserving vascular endothelial cell function [11,12], relief of both peripheral neuropathy and insomnia [13,14], preservation of residual renal function [15] and ultimately a survival benefit [3]. These effects are due to the better quality of dialysis fluid, the greater efficiency of removing uremic accumulates and the better hemodynamic stability during treatment resulting in prevention of dialysis-related hypotension.…”
Section: Expectation For Online Hdf From the Japanese Perspectivementioning
confidence: 99%
“…This dysregulation in homeostasis might impact sleep in various ways. 50,51 It has been seen that in patients with CKD, the serum levels of orexin levels (a neuropeptide associated with arousal) are increased. 52 It has been suggested that this increased level may lead to increased periods of wakefulness that can be associated with insomnia.…”
Section: Insomnia Disordermentioning
confidence: 99%